SPOC alert - when chromosomes get the wrong direction - Caydasi, Ayse Koca; Pereira, Gislene (Experimental cell research, 2012)
The asymmetrically dividing budding yeast relies upon the alignment of the mitotic spindle along the mother to daughter cell polarity axis for the fidelity of chromosome segregation during mitosis. In the case of spindle misalignment, a surveillance mechanism named the spindle position checkpoint (SPOC) prevents cells from exiting mitosis through the inhibition of the mitotic exit network (MEN). MEN is a signal transduction pathway that mediates mitotic exit through fully activation of the Cdk-counteracting phosphatase Cdc14. In this mini-review, we briefly describe the mechanisms leading to mitotic exit in budding yeast cells focusing on the control of MEN by the SPOC. In addition, we summarize the recent advances in the molecular understanding of SPOC regulation and discuss whether similar checkpoints may exist in higher eukaryotic cells that undergo asymmetric divisions.
Gesehen am 15.05.2017